REGARD CRITIQUE SUR LES DEBOIRES DES REVENDICATIONS PROFESSIONNELLES DE L’ASSOCIATION DU PERSONNEL SCIENTIFIQUE DE L’UNIVERSITE DE KISANGANI EN RDC : Diagnostic et perspectives - Loosa Bolamba, Sébastien; Malwilo, Ramazani (IJRDO - Journal of Social Science and Humanities Research, 2018)
The Association of the scientific personnel of the University of Kisangani is undoubtedly known like one of the most claiming corporations among those composing the University of Kisangani. Thus one can count in his credit several actions in this direction from which the benefit take advantage even other corporations (APUKIS, PATO). Nevertheless, it is since nearly five years that its situation knows a spectacular and worrying reversal. All the strikes and other actions initiated regularly by the ASUKIS nothing but do show confused exits. Reason for which, we undertake this study in the objective to determine the major causes of what we describe as "Vexation", of the actions of claims of the ASUKIS, before releasing from them the consequences which will lead to reflexions which, in their turn, will open the ways to us towards prospects for solutions to be considered.